Exposure Knowledge and Risk Perception of RF EMF - Freudenstein, Frederik; Wiedemann, Peter M.; Varsier, Nadège (Frontiers in Public Health, 2015)
The presented study is part of the EU Project LEXNET (Low EMF Exposure Future Networks), which deals among other things with the issue of whether a reduction of the radiofrequency (RF) electro-magnetic fields (EMF) exposure will result in more acceptance of wireless communication networks in the public sphere. We assume that the effects of any reduction of EMF exposure will depend on the subjective link between exposure perception and risk perception. Therefore we evaluated respondents’ risk perceptions of different RF EMF sources and their subjective knowledge about various exposure characteristics with regard to their impact on potential health risks. The results show that participants are more concerned about base stations than about all other RF EMF sources. Concerning the subjective exposure knowledge the results suggest that people have a quite appropriate impact model. The question how RF EMF risk perception is actually affected by the knowledge about the various exposure characteristics was tested in a linear regression analysis. The regression indicates that these features - except distance - do influence people’s general RF EMF risk perceptions. In addition, we analyzed the effect of the quality of exposure knowledge on RF EMF risk perception of various sources. The results show a tendency that better exposure knowledge leads to higher risk perception, especially for mobile phones. The study provides empirical support for models of the relationships between exposure perception and risk perception. It is not the aim to extrapolate these findings to the whole population because the samples are not exactly representative for the general public in the participating countries.